Prayer Has Spoiled Everything : Possession, Power, and Identity in an Islamic Town of Niger - Masquelier, Adeline Marie, 1960- (Book collections on Project MUSE., 2001)
An ethnographic and historical account of bori spirit possession and its relation to Islam, colonialism, and the state.